A COMPARISON OF TECHNIQUES OF BORON REMOVAL FROM WATER AND WASTEWATER - Fadaei, Abdolmajid (UI Scholars Hub, 2022)
Boron is a vital trace element required by plants, humans, and animals. It is also a significant element used in several industries. Along with the widespread usage of boron, boron waste progressively contaminates the potable water sources as well as causing a chain of environmental and health challenges to occur. This study reviews the techniques used for boron removal from aqueous solutions, including ion exchange, resin adsorption, reverse osmosis (RO), electrocoagulation, microfiltration, chemical coagulation, solvent extraction, electro dialytic, and hybrid processes. A review search was carried out from the databases Scopus, PubMed, Web of Knowledge, and Embase using the following key words: “Boron removal”, “saline water”, “wastewater”, “desalination, “membrane”, “adsorption”, “seawater” “hybrid process”, and “groundwater. Boron could be effectively eliminated using membrane treatments, such as RO, electrodialysis and microfiltration with elimination efficiency of 79-99.6%. Based on the findings of this study, the highest and lowest removal efficiency of boron using RO and resin techniques was 5.1-87% and 99.6%, respectively. The RO process is an appropriate technique for seawater desalination along with boron. Adsorption methods are only effective for aqueous solutions with low boron levels and mineral levels when the objective is to avoid repeated regeneration operations limitation. The highest concentration of boron in waters was found to be 25-100 mg/L in Poland, and the lowest concentration of 0.10-1.99 mg/L was found in Pakistan. These processes can be applied to future work to eliminate boron from saline water and wastewater in both experimental and real-world settings.